Influence of the design aspect of lead-acid battery grids on operational life and actual performance under home operating conditions - ريحاوي, علاء (Latakia University Journal -Engineering Sciences Series, 2025)
“There is a lot of talk about the short lifespan of batteries purchased from the market, despite their high prices, in addition to their many malfunctions, which sometimes lead to a catastrophic battery explosion.” There are many factors affecting this, such as the concentration ratio of the electrolyte and the materials that make up the grids...etc. Lead acid batteries are very inexpensive compared to other industrial technologies. Their economic cost has made them very attractive in various industries. Although high current is not an issue, lead acid batteries are a good candidate for electrical storage. For example, in UPS, in industrial electric vehicles such as lift trucks, in small, inexpensive electric vehicles, and any other industry where cost is more important than battery weight. The design aspect is the most important part of the lead-acid battery in terms of the stability of the charging and discharging processes, through which the current condenses around the loop area at the top of the lug and leads to It wears out and then the end of the operational life of the battery. There are different designs that companies consider in order to develop the actual performance of the batteries in terms of stabilizing the electrical voltage and increasing the lifespan. Diversifying these designs to select the optimal design may increase the lifespan by about 50% in home operating conditions and deep cycle.